One Step at a Time: How Model Time Step Significantly Affects Convection‐Permitting Simulations. (5th March 2019) - Barrett, Andrew I.; Wellmann, Constanze; Seifert, Axel; Hoose, Corinna; Vogel, Bernhard; Kunz, Michael
Abstract: We show that there is a strong sensitivity of cloud microphysics to model time step in idealized convection‐permitting simulations using the COnsortium for Small‐scale MOdeling model. Specifically, we found a 53% reduction in precipitation when the time step is increased from 1 to 15 s, changes to the location of precipitation and hail reaching the surface, and changes to the vertical distribution of hydrometeors. The effect of cloud condensation nuclei perturbations on precipitation also changes both magnitude and sign with the changing model time step. The sensitivity arises because of the numerical implementation of processes in the model, specifically the so‐called "splitting" of the dynamics (e.g., advection and diffusion) and the parameterized physics (e.g., microphysics scheme). Calculating one step at a time (sequential‐update splitting) gives a significant time step dependence because large supersaturation with respect to liquid is generated in updraft regions, which strongly affect parameterized microphysical process rates—in particular, ice nucleation. In comparison, calculating both dynamics and microphysics using the same inputs of temperature and water vapor (hybrid parallel splitting) or adding an additional saturation adjustment within the dynamics reduces the time step sensitivity of surface precipitation by limiting the supersaturation seen by the microphysics, although sensitivity to time step remains for some processes. Key Points: Changing model time step affects amount and location of surface precipitation and vertical distribution of hydrometeors Time step choice affects many processes and potentially masks aerosol‐cloud interaction impacts Replacing sequential‐update splitting by a hybrid parallel splitting reduces the time step sensitivity